Local Well-Posedness to the Cauchy Problem for an Equation of the Nagumo Type - Vladimir Lizarazo; Richard De la cruz; Julio Lizarazo (The Scientific World Journal)
In this paper, we show the local well-posedness for the Cauchy problem for the equation of the Nagumo type in this equation (1) in the Sobolev spaces Hsℝ. If D>0, the local well-posedness is given for s>1/2 and for s>3/2 if D=0.